(untitled) (Journal of Enam Medical College, 2015)
Background: Azithromycin sensitivity cannot precisely identify the strains of typhoid and paratyphoid fever for successful treatment. Most of the studies show that azithromycin is highly effective in uncomplicated typhoid fever. Very few studies have been carried out in Bangladesh to see the effectiveness and sensitivity of azithromycin in children with uncomplicated typhoid fever. Objective: To assess the clinical response of azithromycin in uncomplicated typhoid fever. Materials and Methods: This randomized clinical trial was conducted in Dhaka Shishu (children) Hospital from January to December 2009. Children between 212 years of age with characteristic clinical presentation of uncomplicated typhoid fever with positive blood culture for S. typhi or S. paratyphi were included in this study. Patients were treated with oral azithromycin 20 mg/kg/day for 7 days in one group and intravenous ceftriaxone 100 mg/kg/day in another group. Effectiveness and sensitivity pattern were documented and compared. Results: Fifty patients were allocated randomly with azithromycin and 48 with ceftriaxone. Twenty two percent of the subjects were below 5 years and 78% above 5 years. Average time of defervescence was 4.44 ± 1.25 days in azithromycin group and 4.38 ± 1.21 days in ceftriaxone group. Response to treatment in both groups was excellent: 94% in azithromycin and 97.9% in ceftriaxone groups. The occurrence of complication was very low in both groups. Eighteen percent showed resistance to azithromycin and 2.1% to ceftriaxone. In azithromycin sensitive group 97.6% showed improvement and in resistant group 77.8% showed improvement. A good percentage of patients who were resistant to azithromycin showed clinical improvement following treatment with this drug. Conclusion: Current study recommends that azithromycin is effective in the treatment of enteric fever in children. The study also shows that some patients resistant to azithromycin showed clinical improvement following treatment with azithromycin. DOI: http://dx.doi.org/10.3329/jemc.v5i1.21495 J Enam Med Col 2015; 5(1): 34-38